2020
DOI: 10.1080/15440478.2020.1848733
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Chemical and Thermal Treatments on the Diss Fiber Hygroscopic Behaviors

Abstract: Diss fibers, also called Ampelodesmos mauritanicus, are one of the least studied fibers in the literature. Indeed, the rare studies discussed have focused on mechanical and physicochemical properties. The present work deals with hygrothermal characterization and the effect of treatments on their behavior. So, untreated and treated Diss fibers with chemical treat-ments (alkaline, silane, and acetic acid) and heat treatment were character-ized by absorption tests by water immersion and others by water vapor adso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…It is known to offer improved load transfer, adhesion, thermal stability, and chemical resistance, making it suitable for long-term, wear-resistant applications. [14][15][16]52 To quantitatively assess this, the Crystallinity Index (CI) was calculated using the following formula:…”
Section: X-ray Diffraction (Xrd) Properties Of Fibersmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known to offer improved load transfer, adhesion, thermal stability, and chemical resistance, making it suitable for long-term, wear-resistant applications. [14][15][16]52 To quantitatively assess this, the Crystallinity Index (CI) was calculated using the following formula:…”
Section: X-ray Diffraction (Xrd) Properties Of Fibersmentioning
confidence: 99%
“…Raw natural fibers are hydrophilic and porous, leading to undesired moisture absorption and the deterioration of typical cementing microstructures. [11][12][13] Thermal, biological, and chemical treatments [14][15][16] have been proposed to enhance fiber durability and efficiency to some extent by removing non-cellulosic components, 14,17 such as the amorphous contents and reducing their porous nature. However, these processes are still not feasible for large-scale applications due to time, cost, and uniformity constraints, thereby limiting their practical use in the construction market.…”
Section: Introductionmentioning
confidence: 99%
“…Salem et al 19 enhanced the surface texture of the jute fibres by subjecting it to NaOH treatment, silane and epoxy treatment, respectively. The hygrothermal property of a new organic diss fibre was experimented by Nouri et al 20 after putting the fibres through heat and few chemical treatments like alkaline, acetic acid and silane respectively. It was found that the hydrophilic characteristics got highly reduced due to the treatments and simultaneously, chemical treatment put a good impact on adsorption fluctuation.…”
Section: Introductionmentioning
confidence: 99%
“…The results of the water sorption kinetic curves proved to be slow as well as fast on the fiber cell wall, exhibiting hysteresis between adsorption and desorption. Here, the different natural fibers exhibited a variable dynamics of water vapor sorption behavior, mainly in more porous matrices, such as cementitious and geopolymeric [ 40 ].…”
Section: Introductionmentioning
confidence: 99%